Seasonal variation of cesium 134 and cesium 137 in semidomestic reindeer in Norway after the Chernobyl accident - Eikelmann, I.M. H.; Bye, K.; Sletten, H. D. (Rangifer, 1990)
The Chernobyl accident had a great impact on the semidomestic reindeer husbandry in central Norway. Seasonal differences in habitat and diet resulted in large variations in observed radiocesium concentrations in reindeer after the Chernobyl accident. In three areas with high values of cesium-134 and cesium-137 in lichens, the main feed for reindeer in winter, reindeer were sampled every second month to monitor the seasonal variation and the decrease rate of the radioactivity. The results are based on measurements of cesium-134 and cesium-137 content in meat and blood and by whole-body monitoring of live animals. In 1987 the increase of radiocesium content in reindeer in Vågå were 4x from August to January. The mean reductions in radiocesium content from the winter 1986/87 to the winter 1987/88 were 32%, 50% and 43% in the areas of Vågå, Østre-Namdal and Lom respectively.